1981
DOI: 10.1021/j150617a015
|View full text |Cite
|
Sign up to set email alerts
|

Moessbauer spectroscopic study of passivated small particles of iron and iron carbide

Abstract: Mossbauer spectra have been recorded at room, liquid-N2, and liquid-He temperatures for iron supported on silica after calcination, reduction, and carburization. "Passivation", i.e., exposure to air, of reduced iron resulted in partial oxidation to /3-FeOOH. Carburization at 300 °C in 3H2:CO produced a mixture of x-Fe6C2 and e'-Fe2.2C in agreement with previous workers. Passivation of these carbides resulted in partial oxidation to either -FeOOH or an amorphous iron gel. These experiments emphasize the great p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
1

Year Published

1981
1981
2020
2020

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(37 citation statements)
references
References 2 publications
4
32
1
Order By: Relevance
“…31 Amelse et al have reported a lower activity for NiFe/SiO 2 than for either single metal. 32 The results of Arai et al, however, show a higher activity, higher selectivity for C 6+ hydrocarbons and a lower selectivity for methane with NiFe/TiO 2 than with the individual components. 22 The difference in activity and selectivity was explained by two competing processes: the formation of C 2 -C 5 hydrocarbons and their hydrogenolysis.…”
mentioning
confidence: 90%
“…31 Amelse et al have reported a lower activity for NiFe/SiO 2 than for either single metal. 32 The results of Arai et al, however, show a higher activity, higher selectivity for C 6+ hydrocarbons and a lower selectivity for methane with NiFe/TiO 2 than with the individual components. 22 The difference in activity and selectivity was explained by two competing processes: the formation of C 2 -C 5 hydrocarbons and their hydrogenolysis.…”
mentioning
confidence: 90%
“…The metal dispersion was measured from the amount of adsorbed H 2 (mmol/g), the metal loading (mmol metal/g), and the adsorption stoichiometry. The dissociative chemisorption of H 2 on Pd (1 H 2 molecule adsorbing on 2 Pd sites, 2Pd + H 2 → 2Pd-H) was used for the H 2 -based dispersion measurements [25,26].…”
Section: Characterizationmentioning
confidence: 99%
“…However, they are much less reactive than o¢-Fe. The remaining pyrophodc behavior of Fe3C particles may be attributed to the following: (1) Fe3C is co-produced with small amounts of a-Fe. The heat generated by this ,-gaction is enough to initiate the oxidation process of Fe3C to oxy-carbides.…”
Section: Marked By Down Arrows In the Mossbauer Data Ofmentioning
confidence: 99%